If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5+6m=53
We move all terms to the left:
5+6m-(53)=0
We add all the numbers together, and all the variables
6m-48=0
We move all terms containing m to the left, all other terms to the right
6m=48
m=48/6
m=8
| 3n=196 | | 3z/7+4=3 | | r/12=0.75 | | 4(u-64)=80 | | x/5+3.5=12 | | 18q=90 | | 62=4y-14 | | 6m=3.0 | | 42x-35=469 | | 20-(1/5)d=(3/10)d+16 | | 7(u+3)=63 | | 7-3x=2x-(5x-7) | | 2g+3g=40 | | 9x-8=8x+7 | | t/4+19=27 | | 8x−2=70 | | 7x-25-6=4 | | 30=6x=11x | | 54+37+x=180 | | 4x+5x=22 | | 3x-3+2=8 | | -13=-5f+48 | | 6.1+w/7=-5.1 | | .20f-14=1 | | 4^(x+1)=32 | | 54+37+x=90 | | 3u-37=4u-68 | | 4^x+1=32 | | 7+a÷3=5 | | -50x+30=330 | | 2/3(3x+12)=40 | | 4x+29=10 |